Investigating the marital satisfaction in terms of gender: A meta-analysis study Evlilik doyumunun cinsiyet açısından incelenmesi: Bir meta-analiz çalışması - Haylı, Rüstem Göktürk; Durmuş, Emine; Kış, Ali (Journal of Human Sciences, 2017)
The purpose of this research is to apply a meta-analysis to determine whether there is a difference in marital satisfaction according to gender. For this purpose, 64 theses about the subject of marriage satisfaction was reached from the databases of National Thesis Center of the Council of Higher Education. 27 theses, which include with gender variables and data that correspond to the coding protocol included in meta-analysis. The sample of the study consisted of 6,755 people including 3418 female (50,6%) and 3337 male (49,4%). The effect size of marriage satisfaction by gender was determined by using the Standardized Mean Difference (SMD) analysis method known as Cohen’s d in the literature. As a result of Egger’s Regression Test, Orwin’s Fail-Safe N, Duval and Tweedie’s Trim and Fill method and funnel graph, it was determined that there was no publication bias in the research. In the study, a negligible effect size in favour of male was found both the fixed effects model and random effects models (Fixed: d = -0.12 Random: d = -0.08) and the study was heterogeneous (Q = 94.83, p = 0.00, I2 = 72, 58). The findings of the research were discussed in the context of the relevant field and some suggestions were presented. Extended English abstract is in the end of PDF (TURKISH) file. Özet Bu araştırmanın amacı, evlilik doyumunda cinsiyete göre fark olup olmadığını belirlemek için bir meta-analiz uygulamaktır. Bu amaçla Yükseköğretim Kurulu Başkanlığı Ulusal Tez Merkezi Veri Tabanından evlilik doyumunu konu alan 64 teze ulaşılmıştır. Bu tezlerden cinsiyet değişkenine yer verilen ve kodlama protokolüne uyan veriler içeren 27 tez, araştırmaya dahil edilmiştir. Araştırmanın örneklemini 3418’i kadın (%50,6), 3337’si erkek (%49,4) olmak üzere toplam 6755 kişi oluşturmaktadır. Evlilik doyumunun cinsiyete göre etki büyüklüğü, alan yazında Cohen d olarak bilinen Standardize Ortalamalar Farkı (SOF) analiz yöntemi kullanılarak belirlenmiştir. Yayın yanlılığını belirlemek amacıyla uygulanan Egger’in Regresyon Testi, Orwin’in Güvenli N Sayısı, Duval ve Tweedie’nin Kırp ve Doldur yöntemi ve huni grafiği sonucunda araştırmada yayın yanlılığı olmadığı saptanmıştır. Araştırmada hem sabit etkiler hem de rastgele etkiler modeline göre erkekler lehine önemsiz düzeyde (SEM: d=-0.12 REM: d=-0.08) bir etki büyüklüğü saptanmış ve araştırmanın heterojen (Q=94.83, p=0,00; I2= 72,58) olduğu belirlenmiştir. Araştırmanın bulguları ilgili alan yazın çerçevesinde tartışılmış ve birtakım öneriler sunulmuştur.